Anti-synthetase syndrome is associated with a higher risk of hospitalization among patients with idiopathic inflammatory myopathy and COVID-19 - Wu, Wanlong; Wang, Runci; Xie, Cuiying; Chen, Yi; Teng, Xiangyu; Sun, Shuhui; Xu, Wenwen; Fu, Yakai; Ma, Yiyangzi; Xu, Antao; Lyu, Xia; Ye, Yan; et al. (Frontiers in Immunology, 2024)
Data with fine granularity about COVID-19 related outcome and risk factors were still limited in idiopathic inflammatory myopathies (IIMs) population. This study aimed to investigate clinical factors associated with hospitalised and severe COVID-19 in patients with IIMs, particularly those gauged by myositis-specific antibodies.This retrospective cohort study was conducted in Renji IIM cohort in Shanghai, China, under an upsurge of SARS-CoV-2 omicron variant infection during December 2022 to January 2023. Clinical data were collected and analysed by multivariable logistic regression to determine risk factors. High-dimensional flow cytometry analysis was performed to outline the immunological features.Among 463 infected patients in the eligible cohort (n=613), 65 (14.0%) were hospitalised, 19 (4.1%) suffered severe COVID-19, and ten (2.2%) died. Older age (OR=1.59/decade, 95% CI 1.18 to 2.16, p=0.003), requiring family oxygen supplement (2.62, 1.11 to 6.19, 0.028), patients with anti-synthetase syndrome (ASyS) (2.88, 1.12 to 7.34, 0.027, vs. other dermatomyositis), higher IIM disease activity, and prednisone intake >10mg/day (5.59, 2.70 to 11.57, <0.001) were associated with higher risk of hospitalisation. Conversely, 3-dose inactivated vaccination reduced the risk of hospitalisation (0.10, 0.02 to 0.40, 0.001, vs. incomplete vaccination). Janus kinase inhibitor (JAKi) pre-exposure significantly reduced the risk of severe COVID-19 in hospitalised patients (0.16, 0.04 to 0.74, 0.019, vs. csDMARDs). ASyS patients with severe COVID-19 had significantly reduced peripheral CD4+ T cells, lower CD4/CD8 ratio, less naive B cells yet more class-switched memory B cells compared with controls.ASyS and family oxygen supplement were first identified as risk factors for COVID-19 related hospitalisation in IIMs. JAKi pre-exposure might protect IIM patients against severe COVID-19 complications.